Acute megakaryocytic leukemia: What have we learned. Issue 1 (January 2016) - Hahn, Andrew W.; Li, Bojia; Prouet, Philippe; Giri, Smith; Pathak, Ranjan; Martin, Mike G.
Abstract: Acute megakaryocytic leukemia (AMegL) is a biologically heterogenous subtype of acute myeloid leukemia (AML) that arises from megakaryocytes. Improvements in the accuracy of diagnosing AMegL as well as interest in the molecular analysis of leukemias have led to an increased amount of data available on this rare AML subtype. In this review, we will analyze the diverse molecular features unique to AMegL and how they have influenced the development of novel treatment strategies, including polyploidization. The review will also consider the data available on clinical outcomes in AMegL and how it is a poor individual prognostic factor for AML. Finally, the role of allogeneic hematopoietic stem cell transplant in AMegL will be explored.